Determination of the Spectral Index of Ergodicity of a Birth-and-Death Process - Kartashov, M. V. (Ukrains’kyi Matematychnyi Zhurnal, 2000)
We obtain a new explicit relation for the calculation of the spectral index of ergodicity of a birth-and-death process with continuous time. The calculation of the index is reduced to the solution of an optimization problem of nonlinear programming that contains the infinitesimal matrix of the process. As an example, we use the proposed method for finding the exact values of the indices of exponential ergodicity for certain Markov queuing systems.